The Schwarz Chaotic Relaxation Method with Inexact Solvers on the Subdomains (Journal of Computational Mathematics, 1999)
In this paper, a S-CR method with inexact solvers on the subdomains is presented, and then its convergence property is proved under very general conditions. This result is important because it guarantees the effectiveness of the Schwarz alternating method when executed on message-passing distributed memory multiprocessor system.
Keywords: S-CR method; Chaotic algorithm; Inexact solvers.